Problem-based Learning dengan Mutimedia Interaktif untuk Mengatasi Rendahnya Motivasi Belajar Matematika - Ilmiah, Mariatul (Postulat : Jurnal Inovasi Pendidikan Matematika, 2022)
This research was conducted with the aim of overcoming the low learning motivation of students in mathematics through learning with the Problem Based Learning model with interactive multimedia. The subjects of this study were students of Class X Accounting at SMK Negeri 1 Wonorejo, which was located on Jl. PP Al-Yasini Kluwut, Wonorejo District, Pasuruan Regency with a total of 33 students. The research method used is quantitative descriptive analysis. The instruments used in this research were the students' learning motivation questionnaire and formative tests. The learning motivation questionnaire is used to find out whether students' learning motivation is still low after implementing problem based learning models with interactive multimedia. Meanwhile, formative tests are used to see the achievement of student learning objectives. The results showed that 30.3% of students belonged to the very high category and 69.7% of students belonged to the high category. Whereas for formative test results at the first meeting, it was found that 39.4% of students were classified as very good criteria, 45.5% of students were classified as good criteria, and 15.1% of students were classified as sufficient criteria. While the results of the second meeting test 48,5% of students got test results with very good criteria, 42,4% of students got test results with good criteria, and 9.1% of students still got test results with sufficient criteria. From the research results it can be concluded that problem based learning with interactive multimedia can overcome the low motivation to learn mathematics. Keywords: problem based learning, learning motivation, interactive multimedia